Bhutan: Fast Emerging as a Trafficking Centre. Issue 2 (December 2017) - Wangmo, Tandin
Bhutan – A kingdom defined as Shangri-La with a happiness index – is emerging as a centre for trafficking, especially for forced labour and commercial sexual exploitation. A porous border with neighbouring countries where sex-trafficking is rampant, gender inequality, a demand for girls with Oriental features and fair skin, and the institution of Drayang are the root causes for prostitution in Bhutan.